Childhood Drug and Non-Drug Poisoning in Nigeria: An Economic Appraisal - Ifunanya Ikhile; Ifenyinwa Chijioke-Nwauche; Orish Ebere Orisakwe (Ubiquity Press, 2019)
Background: The dearth of information on the economic cost of childhood poisoning in sub-Saharan Africa necessitated this study. Objective: This study has investigated the prevalence of childhood drug and non-drug poisoning, treatment modalities and economic costs in Nigeria. Method: A retrospective study of childhood drug and non-drug poisoning cases from January 2007 to June 2014 in the University of Port Harcourt Teaching Hospital (UPTH), Port Harcourt, Nigeria was carried out. Medical records were analysed for demographic and aetiological characteristics of poisoned children (0-14 years of age), as well as fiscal impact of poisoning cases. Findings: Of the 100 poisoned patients, 46% were male and 54% female, with female/male ratio of 1.17:1. Most of the children were under five years of age. Paracetamol, amitriptyline, chlorpromazine, ferrous sulphate, kerosene, organophosphates, carbon monoxide, snake bite, alcohol and rodenticides were involved in the poisoning. The average cost of poison management per patient was about $168, which is high given the economic status of Nigeria. Conclusion: Childhood poisoning is still a significant cause of morbidity among children in Nigeria and accounts for an appreciable amount of health spending, therefore preventive strategies should be considered.